2017
DOI: 10.1075/pc.17009.gri
|View full text |Cite
|
Sign up to set email alerts
|

Temporal connectives and verbal tenses as processing instructions

Abstract: In this paper, we aim to enhance our understanding about the processing of implicit and explicit temporal chronological relations by investigating the roles of temporal connectives and verbal tenses, separately and in interaction. In particular, we investigate how two temporal connectives (ensuite and puis, both meaning ‘then’) and two verbal tenses expressing past time (the simple and compound past) act as processing instructions for chronological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 38 publications
0
18
1
Order By: Relevance
“…In sum, up to now existing experimental and empirical studies focusing on individual verb tenses showed the following: (1) both the French Passé Simple et Passé Composé trigger more frequently chronological than synchronous relations (Grisot, 2017;Grisot & Blochowiak, 2019), (2) the French Imparfait signals more frequently synchronous than chronological relations (Grisot, 2017), (3) the English Simple Past was found either to signal equally frequently chronological and synchronous relations (Grisot, 2017) or to trigger more frequently chronological than synchronous relations (Feller et al 2019;Madden & Zwaan, 2003;Magliano & Schleich, 2000;Author1, under review), and (4) the English Past Progressive was found either to trigger equally frequently chronological and synchronous relations (Madden & Zwaan, 2003;Author1, under review) or to trigger more frequently chronological than synchronous relations (Feller et al 2019;Magliano & Schleich, 2000). These results are insufficient to understand the role of verb tenses for temporal relations because they show neither a monolingual not cross-linguistic comprehensive picture of all verb tenses and because they seem to be contradictory.…”
Section: Overview Of the Current State Of The Researchmentioning
confidence: 96%
See 4 more Smart Citations
“…In sum, up to now existing experimental and empirical studies focusing on individual verb tenses showed the following: (1) both the French Passé Simple et Passé Composé trigger more frequently chronological than synchronous relations (Grisot, 2017;Grisot & Blochowiak, 2019), (2) the French Imparfait signals more frequently synchronous than chronological relations (Grisot, 2017), (3) the English Simple Past was found either to signal equally frequently chronological and synchronous relations (Grisot, 2017) or to trigger more frequently chronological than synchronous relations (Feller et al 2019;Madden & Zwaan, 2003;Magliano & Schleich, 2000;Author1, under review), and (4) the English Past Progressive was found either to trigger equally frequently chronological and synchronous relations (Madden & Zwaan, 2003;Author1, under review) or to trigger more frequently chronological than synchronous relations (Feller et al 2019;Magliano & Schleich, 2000). These results are insufficient to understand the role of verb tenses for temporal relations because they show neither a monolingual not cross-linguistic comprehensive picture of all verb tenses and because they seem to be contradictory.…”
Section: Overview Of the Current State Of The Researchmentioning
confidence: 96%
“…As for French, Grisot and Blochowiak (2019) investigate the role of French verb tenses and of the presence and absence of temporal connectives, separately and in interaction, as processing instructions for chronological relations in French, by means of a self-paced reading experiment and an offline evaluation experiment. They test how two past time verb tenses (the Passsé Simple and the Passé Composé) and the presence and absence of two specialized connectives (puis 'then' and ensuite 'then') influence the processing and acceptability of short narrative contexts.…”
Section: Overview Of the Current State Of The Researchmentioning
confidence: 99%
See 3 more Smart Citations